European cities in dynamic competition. Theory and case studies on urban governance, strategy, cooperation and competitiveness. - (:unkn) unknown (Springer, 2018)
World population and the number of city dwellers are steadily growing. Globalization and digitalization lead to an increased competition for skilled and creative labor and other economic resources. This is true not only for firms, but increasingly also for cities. The book elaborates on resulting challenges and opportunities for urban management from the European perspective, and discusses theories, methods and tools from business economics to cope with them. Contributions in this volume come from scholars and practitioners of economics, business administration and urban management, and cover aspects ranging from urban dynamics to city marketing. They draw on experiences from several European cities and regions, and discuss strategies to improve city performance including Open Government, Smart City, cooperation and innovation. The book project was initiated and carried out by the Center for Advanced Studies in Management (CASiM), the interdisciplinary research center of HHL Leipzig Graduate School of Management. It is addressed to scholars and managers in Europe and beyond, who will benefit from the scientific rigor and useful practical insights of the book.
Keywords: Stadt; Marketing; Standort; Wettbewerb; Stadtentwicklung; Fallstudie; Urban Governance; Städtewettbewerb; Wirtschaftsstandort; Standortpolitik; Stadtentwicklungspolitik; Open Government; Stadtmanagement; Smart City